Covid-19 Countermeasures And Handling Policy: Maqashid Syariah Perspective - Sandya Mahendra; Tegar Wahyudi; Moh. Indra Bangsawan (Konsorsium LPPM Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
The Covid-19 has become a threat to the sustainability of human life so that the government/ruler is obliged to guarantee the protection of the rights of the people. This research aims to: 1). Describe the policy for the countermeasures and handling of Covid-19; 2). Describe the policy for the countermeasures and handling of Covid-19 from the perspective of Maqashid Syariah. This research is normative legal research conducted by examining library materials or secondary data. The approach used is the statutory approach and the conceptual approach. The current policy for countermeasures and handling Covid-19 marked by the formation of the Task Fore for the Acceleration of Handling Covid-19 through Presidential Decree No. 7 of 2020 and the imposition of restrictions on community activities through Instruction of the Minister of Home Affairs (Mendagri) Number 27 of 2021 concerning the Enforcement of Restrictions on Community Activities Level 4, Level 3, Level 2 Covid-19 in the Java and Bali Regions. The policy for the countermeasures and handling of Covid-19 in the perspective of Maqashid Syariah has been fulfilled in ensuring the protection of people’s rights in the five main elements of human life (din, nafs, nasl, masl, and ‘aql) expect an-nasl in terms of maintaining offspring which during the pandemic the divorce rate continued to increase, in 2015 as many as 5.89 percent of married couples divorced and rose to 6.4 percent in 2020. Therefore, the Government needs to optimize the policy for the countermeasures and handling of Covid-19 so that it can become an important part of the government strategy aimed at ensuring the protection of people’s rights in the five main elements of Maqashid al-Syari’ah.